Mental health self‐disclosure: From stigma to empowerment. Issue 8 (10th May 2022) - Hauer, Karen E.; Hung, Erick
Abstract : Hauer and Hung argue that it is time to confront and disrupt structures within medicine that perpetuate mental health stigma and cause harm.